Does Fighting Back Still Matter? The Canadian Autoworkers, Capitalist Crisis and Confrontation - Fowler, Tim (Capital & Class, 2012)
This article examines the round of collective bargaining that took place between the Canadian Autoworkers (CAW), Canada’s largest private-sector union, and the ‘Big Three’ auto manufacturers (Ford, Chrysler, and General Motors) during the most recent crisis of capitalism (sometimes popularly referred to as the ‘Great Recession’). During this round of bargaining, the union made concessions in order to secure production; the article argues what while this may have represented a short-term success, in the long run the union has implicitly bought into the logics of neoliberalism, which will have disastrous consequences for both the union and the larger labour movement.
Keywords: Autoworkers; Neoliberalism; capitalist crisis; union renewal